Echo-word formation in Bangla - Dastidar, Kuntala Ghosh (Nepalese Linguistics, 2018)
This paper describes and analyzes echo-word formation in Bangla, one of the eastern Indo-Aryan languages of South Asia. Echo-word formation, one kind of partial reduplication, has lexical as well as syntactic implications in Bangla grammar. More specifically, this paper investigates different functions of this partial reduplication and presents its unified account in the grammatical system of Bangla.